Patient-Reported Outcomes in Patients with Chronic Kidney Disease and Kidney Transplant—Part 1 - Tang, Evan; Bansal, Aarushi; Novak, Marta; Mucsi, Istvan (Frontiers in Medicine, 2018)
Chronic kidney disease (CKD) is a complex medical condition that is associated with several comorbidities and requires comprehensive medical management. Given the chronic nature of the condition, its frequent association with psychosocial distress, and its very significant symptom burden, the subjective patient experience is key toward understanding the true impact of CKD on the patients’ life. Patient-reported outcome measures are important tools that can be used to support patient-centered care and patient engagement during the complex management of patients with CKD. The routine collection and use of patient-reported outcomes (PROs) in clinical practice may improve quality of care and outcomes, and may provide useful data to understand the disease from both an individual and a population perspective. Many tools used to measure PROs focus on assessing health-related quality of life, which is significantly impaired among patients with CKD. Health-related quality of life, in addition to being an important outcome itself, is associated with clinical outcomes such as health care use and mortality. In Part 1 of this review, we provide an overview of PROs and implications of their use in the context of CKD. In Part 2, we will review the selection of appropriate measures and the relevant domains of interest for patients with CKD.